Deregulated micrornas are associated with patient survival and predicted to target genes that modulate lung cancer signaling pathways - Souza, Cristiano P. [UNESP]; Cinegaglia, Naiara C. [UNESP]; Felix, Tainara F. [UNESP]; Evangelista, Adriane F.; Oliveira, Rogério A. [UNESP]; Hasimoto, Erica N. [UNESP]; Cataneo, Daniele C. [UNESP]; Cataneo, Antônio J. M. [UNESP]; Neto, Cristovam Scapulatempo; Viana, Cristiano R.; de Paula, Flávia E.; Drigo, Sandra A. [UNESP]; et al. (MDPI, 2020)
(1) Background: Although the advances in diagnostic and treatment strategies, lung cancer remains the leading cause of cancer-related deaths, worldwide, with survival rates as low as 16% in developed countries. Low survival rates are mainly due to late diagnosis and the lack of effective treatment. Therefore, the identification of novel, clinically useful biomarkers is still needed for patients with advanced disease stage and poor survival. Micro(mi)RNAs are non-coding RNAs and potent regulators of gene expression with a possible role as diagnostic, prognostic and predictive biomarkers in cancer. (2) Methods: We applied global miRNA expression profiling analysis using TaqMan® arrays in paired tumor and normal lung tissues (n = 38) from treatment-naïve patients with lung adenocarcinoma (AD; n = 23) and lung squamous cell carcinoma (SCC; n = 15). miRNA target genes were validated using The Cancer Genome Atlas (TCGA) lung AD (n = 561) and lung SCC (n = 523) RNA-Seq datasets. (3) Results: We identified 33 significantly deregulated miRNAs (fold change, FC ≥ 2.0 and p < 0.05) in tumors relative to normal lung tissues, regardless of tumor histology. Enrichment analysis confirmed that genes targeted by the 33 miRNAs are aberrantly expressed in lung AD and SCC, and modulate known pathways in lung cancer. Additionally, high expression of miR-25-3p was significantly associated (p < 0.05) with poor patient survival, when considering both tumor histologies. (4) Conclusions: miR-25-3p may be a potential prognostic biomarker in non-small cell lung cancer. Genes targeted by miRNAs regulate EGFR and TGFβ signaling, among other known pathways relevant to lung tumorigenesis.
Keywords: Lung cancer; MicroRNAs; Pathways; Survival; Target genes